Benchmarking in the Context of National Innovation Systems: Purpose and Pitfalls - Markus Balzat (Universität Augsburg, Institut für Volkswirtschaftslehre, 2003)
Recent contributions to the literature of national innovation systems (NIS) reflect growing research interests in cross-country comparisons, in particular so in performance comparisons across national innovation systems. Although such comparisons differ significantly in terms of methodological aspects, most of them are labeled as benchmarking studies. But not only the use of this technical term can be problematical; the very task of comparing NIS is now under debate as well. It is the purpose of this paper to discuss the usefulness of benchmarking studies carried out within the framework of national innovation systems (NIS benchmarking).
urn:nbn:de:bvb:384-opus4-712208
Keywords: P51; O30; O10; 330; innovation; national innovation systems; performance measurement; Innovation; Innovationspolitik; Systemvergleich; Benchmarking; Kritik